Performing Yeast One-Hybrid Library Screens - Fuxman Bass, Juan I. (Cold Spring Harb Protoc, 2016)
Yeast one-hybrid (Y1H) assays are used to identify which transcription factor (TF) “prey” molecules can bind a DNA fragment of interest that is used as “bait”. Y1H assays involve introducing plasmids that encode TFs into a yeast “bait strain” in which the DNA fragment of interest is integrated upstream of one or more reporters, and activation of these reporters indicates that a TF–DNA interaction has occurred. These plasmids express each TF as a hybrid protein (hence the “one-hybrid” name) fused to the activation domain (AD) of the yeast TF Gal4. The AD moiety activates reporter expression even if the TF to which it is fused typically functions as a repressor. Here, we describe how to perform a Y1H screen of a library of cDNA fragments cloned into a pPC86 plasmid expressing the protein encoded by the cDNA as an AD fusion. The method assumes availability of either commercially available libraries or libraries generated in house using mRNA extracted from a tissue of interest. We also assume that users have access to a yeast bait strain that possesses the DNA fragment of interest integrated upstream of two different reporters—HIS3, an auxotrophic marker, and LacZ, a colorimetric marker that changes colorless X-gal into a blue compound. Briefly, the screen involves transforming the AD-cDNA library into the yeast bait strain, identifying colonies that show activation of both reporters, retesting the interaction in a freshly grown bait strain, and sequencing the cDNA insert to identify the interacting TF.